Inhibition of inhaled halloysite nanotube toxicity by trehalose through enhanced autophagic clearance of p62. Issue 3 (16th March 2019) - Rong, Rui; Zhang, Yongming; Zhang, Yunjiao; Hu, Yi; Yang, Wenjie; Hu, Xiaowen; Wen, Longping; Zhang, Qixing
Abstract: Nanomaterials are widely used in an ever-increasing number of consumer and industrial products. It is therefore essential that the toxic effects of nanomaterials are understood in order to improve product safety. Here we evaluate the toxicity of inhaled halloysite nanotubes (HNTs) by applying a purpose designed inhalation exposure system and succeed in suppressing HNTs toxicity using trehalose. By assessing apoptosis, oxidative stress, inflammatory response, and autophagy, it is found that HNTs can cause sub-chronic toxicity in mice. Further investigations indicate that HNTs induce autophagy blockade that results in the accumulation of sequestosome-1 (p62), which is responsible for the excessive apoptosis, inflammatory response and oxidative stress. We found that p62 can be eliminated by trehalose and the application of trehalose in vitro and in vivo successfully inhibits toxicity by accelerating the clearance of p62. Trehalose shows great potential for reducing nanoparticle toxicity.